Phage therapy for intestinal infections: efficacy, challenges, and future directions in translational research - Wang, Xiaoqing; Li, Jingjing; Ge, Zimo; Fan, Junhao; Ma, Dongdao; Cao, Huiru; Shen, Jiawen; Wang, Yange; Liu, Zhonghua; Gomaa, Salwa E.; Li, Xianghui; Ji, Xinying; et al. (Frontiers in Microbiology, 2025)
Phage therapy has emerged as a promising alternative to conventional antibiotics for combating intestinal bacterial infections, especially in the era of rising antimicrobial resistance. Despite its therapeutic potential, the clinical translation of phage therapy remains hindered by limited large-scale trial data and incomplete mechanistic understanding. This review systematically evaluates the efficacy of phage therapy in animal models of intestinal diseases, encompassing bacterial infection-induced diarrhea (e.g., cholera, typhoid fever), bacterial enteritis, and sepsis. By synthesizing evidence from bacterial colonization assays, histopathological analyses, and disease severity assessments, we highlight features such as phage-mediated pathogen clearance, changes in inflammatory factors, and intestinal pathology. Furthermore, challenges including phage selection difficulties, host specificity issues, and safety considerations are discussed, along with future research directions aimed at bridging the gap between experimental models and clinical applications.